Answer:
x = 2, y = -1
Solve the following system:
{-y + x = 3 | (equation 1)
-y + 2 x = 5 | (equation 2)
Swap equation 1 with equation 2:
{2 x - y = 5 | (equation 1)
x - y = 3 | (equation 2)
Subtract 1/2 × (equation 1) from equation 2:
{2 x - y = 5 | (equation 1)
0 x - y/2 = 1/2 | (equation 2)
Multiply equation 2 by 2:
{2 x - y = 5 | (equation 1)
0 x - y = 1 | (equation 2)
Multiply equation 2 by -1:
{2 x - y = 5 | (equation 1)
0 x + y = -1 | (equation 2)
Add equation 2 to equation 1:
{2 x + 0 y = 4 | (equation 1)
0 x + y = -1 | (equation 2)
Divide equation 1 by 2:
{x + 0 y = 2 | (equation 1)
0 x + y = -1 | (equation 2)
Collect results:
Answer: |
| {x = 2
y = -1
I believe that this is truly the answer.